PENGARUH PENGELOLAAN MASALAH PELANGGAN, EDUKASI PELANGGAN DAN PARTISIPASI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Jatmiko, M. Roby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This research analyses the influence of customer participation, customer problem management,Â  and educational customer to customer loyalty. Technique of sampling applied is accidental sampling method. The responders in this research are 121 responders, and all responder are customers of Vitalac. Tool of data analysisâs used is using computer program of SPSS.The result of data analysis shows that the model developed and the research result can be accepted.Â  Hereinafter, the result proves that there is positive influence of customer participation, customer problem management,Â  and educational customer to customer loyalty